(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the methods of forming the spiritual and moral culture of young people in the new Uzbekistan, the main subject of art and ethics is man, if art reflects the goals and interests of a person, opinions, feelings, inner experiences, Morality is embedded in the core of human social relations and relationships, and it is explained that morality is necessary in life and society.